بروتوكول المصادقة في اتصال جهاز إلى جهاز في شبكات LTE - أحمد, أحمد; ستيتي, أماني (Latakia University Journal -Engineering Sciences Series, 2018)
A constant need to increase the network capacity for meeting the growing demands of the subscribers has led to the evolution of cellular communication networks from the first generation (1G) to the fifth generation (5G). There will be billions of connected devices in the near future. Demanding higher data rates, lesser delays، enhanced system capacity and superior throughput. The available spectrum resources are limited and need to be flexibly used by the mobile network operators (MNOs) to cope with the rising demands. The solution was the device-to-device connections. Enabling Device to Device (D2D) communications over LTE-A networks (Long Term Evaluation-Advanced) can provide many benefits in terms of throughput، energy consumption، traffic load. It also enables new commercial services. Such as location-based advertising. For these reasons، D2D communications has become A hot topic in both the academic and industrial communities. However، many research works are focused on node discovery، radio resource management، and other aspects، while the issue of security is less addressed. In this article،, we intend to provide an overview of the security architecture، threads، and requirements، and authentication protocols. الحاجة الماسة لزيادة قدرة الشبكة من أجل توفير المعلومات والمتطلبات للمشتركين أدى إلى تطوير شبكات الاتصال الخلوية من الجيل الأول إلى الجيل الخامس. ففي المستقبل القريب سيكون هناك مليارات من الأجهزة المتصلة والتي تتطلب معدل بيانات أكبر، زمن تأخير أقل، قدرة نظام أعلى إضافة إلى انتاجية أفضل. ولكن الموارد المتاحة محدودة وتحتاج إلى استخدام مرن من قبل مشغلي الشبكات المتنقلة للتعامل مع المطالب المتزايدة، والحل كان بتقنية الاتصال جهاز إلى جهاز، تفعيل اتصال جهاز إلى جهاز عبر الشبكات المتقدمة طويلة الأمد (Long Term Evaluation-Advanced) LTE-A يمكن أن يعود بالعديد من الفوائد من خلال الإنتاجية، استهلاك الطاقة، حمل حركة المرور وأيضا الخدمات التجارية الجديدة مثل الإعلانات المعتمدة على الموقع. أصبح موضوع الاتصال جهاز إلى جهاز موضوع مهم سواء في الأوساط الأكاديمية والصناعية، والعديد من الأبحاث تركز على اكتشاف العقدة وإدارة الموارد الراديوية والجوانب الأخرى، في حين أن مسالة الأمن هي الأقل معالجة. في هذا البحث، سوف نقدم لمحة عامة عن البنية الأمنية لاتصال جهاز إلى جهاز، التهديدات، المتطلبات، وبروتوكولات المصادقة.